Mould filling and pressure distribution for polymer resins - Mohd, Alias; Hindle, C.; Wan Yusoff, Wan Ahmad Yusmawiza (Trans Tech Publications, Switzerland, 2011)
The application of simulation software packages for mould design and injection moulding process is becoming importance to optimizing the moulding quality and satisfy market needs. This paper presents the simulation of mould filling and packing for various polymer resin types. The filling and packing pressure phases for different type of polymer resins as well as the flow behaviour of molten resin in the mould cavity were investigated. Three common polymer resins which are amorphous and crystalline thermoplastics were used. Cylinder component cups with variation of wall thicknesses were designed. Two-cavity prototype moulds for cylindrical shape component were constructed by using AutoCAD 2006 including assembly and part drawings. The 3D model was produced by using Autodesk Inventor Professional. The result successfully revealed that polyamide resin required shorter time for filling the cavity and less pressure compared to PS and ABS.